2022
DOI: 10.3390/atmos13101581
|View full text |Cite
|
Sign up to set email alerts
|

The Spatio-Temporal Onset Characteristics of Indian Summer Monsoon Rainfall and Their Relationship with Climate Indices

Abstract: Regional variations of monsoon onset dates across India were analyzed for 67 years (1951–2017) under different modes of climate variations, i.e., El Niño, La Niña, and the Indian Ocean Dipole (IOD), along with flood and drought years using the objective method and statistical techniques. Monsoon onset analysis revealed that the northern, northeastern, and southern parts were highly susceptible to the early onset of La Niña, and the northern and northern northwest parts were highly susceptible to the early onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Therefore, the policy and planningrelated institutions should consider these regions as vulnerable districts, and a highly refined framework must be prepared to mitigate the impacts in the long term. While investigating the intricacies of the monsoon onset, Saini et al (2022) found its relation with the length of the monsoon season and the amount of rainfall [1]. Therefore, in the long term, changing patterns and timing of the monsoon onset can influence the regime of agriculture, disease proliferation, river regime, etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the policy and planningrelated institutions should consider these regions as vulnerable districts, and a highly refined framework must be prepared to mitigate the impacts in the long term. While investigating the intricacies of the monsoon onset, Saini et al (2022) found its relation with the length of the monsoon season and the amount of rainfall [1]. Therefore, in the long term, changing patterns and timing of the monsoon onset can influence the regime of agriculture, disease proliferation, river regime, etc.…”
Section: Discussionmentioning
confidence: 99%
“…LRM was also used to identify monotonic trends and variations in the value of the onset day. The monotonic trend in statistics generally means the consistently increasing or decreasing trend through time and has been used in climate studies also [14,17,18] Additionally, LRM was essential in comparing grid-wise monsoon beginning dates determined by PLRM with dates acquired using the objective technique described and used by Saini et al (2022) [3,19]. Following the SR boundaries defined by Singh and Ranade (2010) [19], the grid-wise monsoon dates were derived for each sub-region (SR) for this research using the field mean approach.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, there has been an increase in the highest recorded temperature observed throughout the monsoon season. In tandem with heightened levels of precipitation, an elevation in the maximum attainable temperature has the potential to amplify the occurrence of torrential rainfall events during the monsoon season 26 . This long-term change in atmospheric parameters, known as climate change, may affect river hydrology and biodiversity.…”
Section: Introductionmentioning
confidence: 99%